Unique Tradition Of Eidul Adha Celebration In Indonesia (Thematic Study Of The Qur'an) - Alam Tarlam; Zaenudin; Jamali (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2023)
Indonesia is a country that has a lot of cultural values in each region, both sacred and non- sacred culture or can be called a unique culture. From time to time, humans have tried to apply their religious beliefs in the form of various rituals or religious traditions as a means to get closer to God, among the rituals performed on the Eid al-Adha Celebration. This article was created with the aim of uncovering various unique cultures or traditions at the time of Id Adha celebrations, which are a lot of unique cultures and celebrations in Indonesia that the author needs to convey as a form of contribution of thought and knowledge in the scientific field. . The method used by the author in this article uses a qualitative descriptive method which is a method that describes the results of existing findings from books, journals, in the field and other sources. The results of this study are that in Indonesia there are many cultures and traditions during the celebration of Eid al-Adha including the Gamelan Sekaten Tradition in Cirebon, the Apitan Tradition in Semarang, the Grebeg Gunungan Tradition in Yogyakarta, the Manten Sapi Tradition in Pasuruan, the Meugang Tradition in Aceh.